2018
DOI: 10.1136/tsaco-2018-000177
|View full text |Cite
|
Sign up to set email alerts
|

Joint management format at the mixed-surgical intermediate care unit: an interrupted time series analysis

Abstract: BackgroundThe management format of the mixed-surgical intermediate care unit (IMCU) affects its performance. A format of combined supervision of surgeons with additional critical care certifications and admitting specialists, named the “joint format”, may herein be a promising new model of specialized critical care. This study aims to assess the performance of the joint management format.MethodsThis observational cohort study compared three IMCU management formats at the stand-alone, mixed-surgical IMCU of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Second, we did not model entire patient trajectories of hospital stay and therefore we did not incorporate the effect of the IMCU or ICU on total hospital (or critical care) days and costs, for example, it may be that, in the absence of the IMCU, the same ICU-admitted patients are discharged from the hospital earlier, reducing total costs. Third, it is important to realise that this study does not account for patient outcomes (eg, mortality), but we have shown before that within this study period patient outcomes were satisfactory, that is, adverse events (IMCU mortality and ICU transfer) were uncommon 11. Fourth, since the organisation of intermediate care differs per hospital, adequate triage to mainly admit high-acuity patients is essential to justly generalise these results to other intermediate care settings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, we did not model entire patient trajectories of hospital stay and therefore we did not incorporate the effect of the IMCU or ICU on total hospital (or critical care) days and costs, for example, it may be that, in the absence of the IMCU, the same ICU-admitted patients are discharged from the hospital earlier, reducing total costs. Third, it is important to realise that this study does not account for patient outcomes (eg, mortality), but we have shown before that within this study period patient outcomes were satisfactory, that is, adverse events (IMCU mortality and ICU transfer) were uncommon 11. Fourth, since the organisation of intermediate care differs per hospital, adequate triage to mainly admit high-acuity patients is essential to justly generalise these results to other intermediate care settings.…”
Section: Discussionmentioning
confidence: 94%
“…Triage for admission is performed by the responsible medical team of the IMCU in collaboration with the admitting specialist. The efficiency and safety of the here-described IMCU is more extensively described in previous publications 10 11. It should be noted that, if IMCUs are not safe, they should not be used, regardless of their (potential) economic benefits.…”
Section: Methodsmentioning
confidence: 94%
“…This supplements earlier research within the same IMCU, which showed that the joint format has an equal efficiency and safety (with a more complex caseload) compared with other formats. 12 …”
Section: Discussionmentioning
confidence: 99%